2010
DOI: 10.1016/j.proeng.2010.03.093
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack growth behavior of surface crack in rails

Abstract: Rolling contact fatigue damages on the surface of rail such as head check, squats are one of growing problems. Since rail fracture can cause derailment with loss of life and property, the understanding of rail fracture mechanisms is important for reducing damages on the surface of rail. In this study, a two-dimentsional computational model was used to simulate the fatigue crack growth behavior at the surface of rail. The model considers the moving contact pressure and tangential force. Normal pressure of 1100M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 8 publications
0
14
0
5
Order By: Relevance
“…Fatigue crack propagation modeling with fatigue life prediction analysis based on fracture mechanics analysis of specific crack growth geometries is one useful method. This method is usually applied by considering quasi‐static loading and boundary conditions, as well as selecting different initial crack sizes, shapes, and crack front orientation based on the physical observations or measurements from actual fractured cases …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue crack propagation modeling with fatigue life prediction analysis based on fracture mechanics analysis of specific crack growth geometries is one useful method. This method is usually applied by considering quasi‐static loading and boundary conditions, as well as selecting different initial crack sizes, shapes, and crack front orientation based on the physical observations or measurements from actual fractured cases …”
Section: Introductionmentioning
confidence: 99%
“…This method is usually applied by considering quasi-static loading and boundary conditions, as well as selecting different initial crack sizes, shapes, and crack front orientation based on the physical observations or measurements from actual fractured cases. [13][14][15][16] Another method is to explore a fatigue initiation analysis approach if the complex dynamic stress applied by the train wheel on the rail steel can be simulated employing 3D dynamic finite element analysis methodology. The railway track system comprises a continuous welded rail mounted with rail clips on sleepers (wooden or concrete) integrated to a track form system.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches about the growth path of the wheel/rail contact fatigue have been reported. The review by Smith et al [2,4] indicated that there was an acute angle between the crack initiation and the direction of train running during the initial stage, and the growth angle increased with the increase of the depth, and, finally, the rail fractured in the direction perpendicular to the surface, as shown in Figure 1(a). Chen et al [5] studied the spalling path of the rail head through slice analysis and concluded that when the cracks grew to a certain depth, they would change their propagation direction and then spread approximately along the right-about with train running direction towards the rail surface; consequently, spalling was formed in the shape of barb, as shown in Figure 1(b).…”
Section: Introductionmentioning
confidence: 99%
“…As for the crack propagation mechanism, Ringsberg et al [17][18][19] studied the microcracks propagation mechanism of the rail surface based on the Hertz theory and the wheel/rail tribology and found that the propagation of microcracks on surface was mainly open mode. With regard to the long cracks, Seo et al [4,20,21] investigated that sliding propagation was their major mode, and their propagation rate increased as the friction coefficient between the wheel and the rail increased.…”
Section: Introductionmentioning
confidence: 99%
“…Crack growth under RCF with a linear elastic fracture mechanics (LEFM) approach (Franklin et al, 2011;Hannes and Alfredsson, 2012) are of great concern in rail life study. There have been a number of investigations that focused on determining the stress intensity factors (SIF) for cracks subjected to RCF (Liu and Hamada, 2011;Seo et al, 2010), which could be a very clear index to show rail crack growth behavior.…”
Section: Introductionmentioning
confidence: 99%